Perancangan Prototype SIBAHAGIA Berbasis Web Menggunakan Design Thinking - Siti Herawati Fransiska Dewi; Ali Muhammad; Angge Firizkiansah; Dita Setiawan (Universitas Sains Indonesia Publishing, 2025)
The Kota Jambi Bahagia flagship programs require a monitoring system that can present clear and structured information on program implementation and realization for various stakeholders. The main issue is the absence of a website interface design that accommodates the different needs of users based on their roles, namely users from implementing government agencies (users from implementing government agencies), coordinators/administrators, and decision-makers. This study aims to design a UI/UX prototype of a website for monitoring the 11 Kota Jambi Bahagia flagship programs based on user experience principles. The research adopts the Design Thinking method, which consists of the empathize, define, ideate, prototype, and test stages. The results include user flows, wireframes, and a high-fidelity prototype that supports activity submission, monitoring, and program realization by OPD users, as well as an executive dashboard for decision-makers. Prototype evaluation is conducted through task-based usability testing. The findings indicate that the proposed prototype effectively supports program monitoring and is easy for users to understand